2020
DOI: 10.37544/0949-8036-2020-07-08-7
|View full text |Cite
|
Sign up to set email alerts
|

Anwendungssichere nanokohlenstoffbasierte Fasermaterialien/Nanocarbon-based fibrous substances that are safe for use

Abstract: Es wird eine Methode vorgestellt, um Sicherheitsaspekte von Prozessen zu untersuchen, mit denen metallische faserverstärkte Verbundwerkstoffe hergestellt und bearbeitet werden. Ziel ist, zu anwendungssicheren Prozessen zu gelangen, indem Gefahren gesundheitsgefährdender Stäube möglichst frühzeitig identifiziert und geeignete Schutzmaßnahmen ausgewählt werden. In der hier untersuchten Anwendung wurden Komposite aus Kupfer (Cu) mit Kohlenstoffnanoröhren (carbon nanotubes, CNTs) oder Kohlenstoffnanofasern (carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Table 14 compiles information on the workplaces and sampling parameters and reports fiber counting results for the nearfield filter samples and the corresponding upper limit concentration estimates. Since microscale fibers were already included in the image evaluation rules, the analysis of the workplace samples WP13 and WP14 performed with our nanofiber-sensitive strategy revealed that a purely microscale fiber fraction caused the observed violation of the exposure limit value for WHO 20 -fibers [37]. For workplaces in which no WHO 20 product fibers were observed in the nearfield, no product fibers were found on personal or farfield samples, either.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Table 14 compiles information on the workplaces and sampling parameters and reports fiber counting results for the nearfield filter samples and the corresponding upper limit concentration estimates. Since microscale fibers were already included in the image evaluation rules, the analysis of the workplace samples WP13 and WP14 performed with our nanofiber-sensitive strategy revealed that a purely microscale fiber fraction caused the observed violation of the exposure limit value for WHO 20 -fibers [37]. For workplaces in which no WHO 20 product fibers were observed in the nearfield, no product fibers were found on personal or farfield samples, either.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, extrapolation to shift values may be necessary. More results of this measurement campaign have been or will be reported in dedicated workplace-and material-related publications [37,40].…”
Section: Discussionmentioning
confidence: 99%